(3JhTjM GdJUMjMs - (3YHO GdhgGH Hf Ydj Hf YHO GdcGai GdeTghQ HGdTHdis; (3Gdfhhj,J (B676 (3g` s ((3jMji Hf eMeO Hf GdYfHQi GdMSjfi s)
(3ChdgG (B:s
(3aEf GdTjN GdEeGe GdQHGfi CHG RcQjG Gdfhhi QVi Gddg Yfg hVY Ydi cJGH GdfHJg cJGHg GdJUMjM hVYkG MSfkG s
(3BNQgG (B:s
(3hgh QGhi UMjM eSde hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs